Answer: B) 4/3
==================================================
Work Shown:
![\displaystyle \lim_(x \to 3) (f^2(x)-4)/(f^2(x)-f(x)-2)\\\\\\\displaystyle \lim_(x \to 3) ((f(x)-2)(f(x)+2))/((f(x)-2)(f(x)+1))\\\\\\\displaystyle \lim_(x \to 3) (f(x)+2)/(f(x)+1)\\\\\\\displaystyle (f(3)+2)/(f(3)+1)\\\\\\\displaystyle (2+2)/(2+1)\\\\\\\displaystyle (4)/(3)\\\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/9s4ugtn26bp5pm1r86sddfhz800quaedc3.png)
Notes:
In step 2, I used the difference of squares rule to factor the numerator. The denominator can be factored through trial and error. The key here is the f(x)-2 terms that show up in each. Those factors cancel in step 3.
Afterward, we apply the substitution rule,
, so basically I plugged in x = 3. Then evaluated f(3) = 2 due to the point (3,2).